Strategi Menghadapi Persaingan Bisnis Pada UMKM Di Kabupaten Tangerang - Puji Rahayu; Joko Supono; Andri Zalmi (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
The basic knowledge and strategies of microenterprise actors are important to help them manage and develop their businesses more effectively. The following section presents basic knowledge and strategies that may be useful for microentrepreneurs. Knowledge of the concepts, characteristics and challenges facing microenterprises, including resource constraints, access to capital and scale of operations. Understanding the local market, competitors, consumer trends and purchasing behavior can help determine the right marketing strategy. Basic issues of financial management, Hopefully, SWOT analysis can help business stakeholders reassess the internal and external factors of the business.